Density of House Dust Mites (HDM) Dermathopagoides sp. In Jatimulya Village South Tambun District Bekasi City - Reza Anindita; Salma Lailatul Amwia; Maulin Inggraini; Dede Dwi Nathalia (UNUSA Press, 2022)
Background: House Dust Mites (HDM) are arthropods that trigger allergies such as asthma and rhinitis. The percentage of these animals as the cause of asthma according to WHO data (2013) is around 50% -80%. Objective: The purpose of this study was to obtain new information about the density of HDM in the city of Bekasi as well as to complement the existing data so that it can be used as a reference in formulating an allergy prevention program caused by HDM. Methods:This study was designedwith a quasi-experimental study research method using a comparative pre-test post-test non-equivalent control group design.The sample in this study was divided into two groups, namely one control group and one treatment group from the sample selected by purposive sampling. The population studied were students of the Hidayatullah Islamic Boarding School inSurabaya. Result: This type of research is quantitative descriptive with a cross-sectional research design. The sample in this study were 9 houses of residents of the village of Jati Bulak, RT 001/ RW 003, Jatimulya Village, Tambun Selatan District. The location points for dust sampling for each house are mattresses, carpets and floors. The working procedure of this research includes the pre-analytic stage in the form of preparation of tools and materials, the analytical stage in the form of HDM examination with the sedimentation method, the post-analytic stage in the form of confirmation of HDM identification. Conclusion:From research result that has been done, it can be concluded that the HDM figures in 9 houses of Jati Bulak villagers RT 001/ RW 003 Jatimulya Village, Tambun Selatan District are in the low category.